Implementasi Kriptografi Hybrida Algoritma RSA dan Vernam Cipher Dalam Pengamanan File Text - Hori Andara; Fera Damayanti; Khairunnisa Khairunnisa (UIN Sumatera Utara, 2022)
Nowadays, The development of the times is in line with the development of computer technology, which means that the storage and delivery of electronic documents is also increasing rapidly. Text files as a form of representation of electronic documents, namely all electronic information created and stored in digital form. The issue of information security in text files is a very crucial issue to be discussed. Especially if the text file sent has important and confidential information. If ignored, the information can be changed or used by irresponsible parties. Therefore, we need a technique or method to maintain the confidentiality of information known as cryptography. Cryptography has two key types, namely symmetric and asymmetric. In this study, the authors combine symmetric and asymmetric keys. The symmetric key has one key, while the asymmetric key has two keys, namely the public key and the private key. Symmetric keys are used to secure text files, while asymmetric keys are used to secure symmetric keys, a process known as hybrid cryptosystem. One of the symmetric algorithms is Vernam Cipher, while the RSA algorithm is one of the asymmetric algorithms. Secured text files are those with the *.txt file format. The results of the system testing in this study show that the time required for text file encryption is directly proportional to the character length of the text file. This means that the longer the text file used, the longer it will take to encrypt and decrypt the text file. Keywords: Cryptopraphy, Hybrid Cryptosystem, Vernam Cipher, RSA